THE DIFFERENCE OF STUDENTS’ LEARNING OUTCOMES USING INQUIRY TRAINING MODEL AND DIRECT INSTRUCTION MODEL - Agnesia M Damanik; Alkhafi Maas Siregar (UNIVERSITAS NEGERI MEDAN, 2013)
The objective of this research was to carry out the difference of students’ learning outcomes using inquiry training model and direct instruction model in physics topic. The research method was quasi experiment. The population was all students at class VIII semester II consist of 9 classes at SMP N 1 Tebing Tinggi. The sample of this research is two classes that consist of 50 students, class VIII-1 as an experiment class and class VIII-2 as a control class and taken by cluster random sampling. Normality of the test result from the both samples was normal and homogeneous, the testing criterion was accepted H0 if -2.012< t’ < 2.012 and refuse H0 in other condition. Here, H0 was refused because t’ is 2.75 and Ha was accepted. So it can be concluded that there was significant difference of students’ learning outcomes using inquiry training model and direct instruction model. Keyword : Inquiry Training Model, Students’ Learning Outcomes